Workplace abuse narratives from dentistry, nursing, pharmacy and physiotherapy students: a multi‐school qualitative study. (17th July 2014) - Rees, C. E.; Monrouxe, L. V.; Ternan, E.; Endacott, R.
Abstract Introduction Previous healthcare student abuse research typically employs quantitative surveys that fail to explore contributory factors for abuse and students' action in the face of abuse. Following a recent qualitative study of medical students' abuse narratives, the current study explores dental, nursing, pharmacy and physiotherapy students' abuse narratives to better understand healthcare workplace abuse. Methods We conducted three individual and 11 group interviews with 69 healthcare students in three Universities to elicit professionalism dilemma narratives. Of 226 professionalism dilemmas elicited, 79 were coded as student abuse. Secondary‐level thematic analysis of the abuse narratives addressed the following questions: What types of abuse experiences do healthcare students narrate? What factors do they cite as contributing to abuse and their responses to abuse? Results Healthcare students reported mostly covert abuse in their narratives. Although narrators described individual, relational, work and organisational factors contributing to abuse, they mostly cited factors relating to perpetrators. Most participants stated that they acted in the face of their abuse, and they mostly cited factors relating to themselves for acting. Students who did nothing in the face of abuse typically cited the perpetrator‐recipient relationship as the main contributory factor. Discussion There are many similarities across the narratives of the five healthcare student groups, suggesting that complex interactional/organisational factors are all‐important when considering how abuse is perpetuated within the healthcare workplace. Although some organisational factors may be difficult to change, we recommend that educational initiatives are a key starting point to tackle healthcare workplace abuse.